Planificación tributaria para el cumplimiento de las obligaciones relacionadas con los aportes de la ley orgánica de ciencia, tecnología e innovación (locti) en empresas del sector de industrias lácteas. Caso venezolano (2013)
The purpose of this research was to analyze tax planning for the fulfillment of obligations related to the contributions of the Law on Science, Technology and Innovation in companies dairy industries supported in law and doctrine represented by Dominguez and Lopez (2002) Rosales (2008), Moya (2006). The research was descriptive and qualitative and quantitative applied, considering a non experimental design transactional documents and descriptive field. The population was 10 companies in the Dairy Industry in Maracaibo. This study revealed that there are various tax planning techniques applicable to the contributions of LOCTI (2010), to be relevant that this contribution corresponds to companies with revenues greater than 100,000 tax units, to apply 0.5% of revenues from dairies. Thus identifying the sanctions regime, remain the responsibility of the Ministry of Popular Power for Science, Technology and Innovation, where fines of up to 50,000 UT 10 UT for those who violate the laws. In these companies apply tax planning procedures, including determination of gross receipts, accounting records and the filing and payment. General guidelines are proposed to optimize tax planning towards the fulfillment of obligations related to the contributions of the Law on Science, Technology and Innovation in companies from dairies.